Comparative Effects of Photobiomodulation Therapy Versus Conventional Antioxidant Supplementation on Serum Glutathione Levels in Euthyroid Chronic Autoimmune Thyroiditis: A Prospective Open-Label Interventional Clinical Trial - Venera Berisha-Muharremi; Bernard Tahirbegolli; Alberta Humolli; Reem Hanna (Antioxidants, 2026)
Background: Chronic autoimmune thyroiditis (CAT) is characterized by persistent autoimmune activity and increased oxidative stress, which may contribute to thyroid follicular injury and disease progression. Photobiomodulation (PBM) has shown potential beneficial effects on thyroid function and autoimmunity; however, its independent effect on systemic antioxidant status, particularly serum glutathione (GSH), has not been established. This study aimed to evaluate the effect of thyroid-directed PBM on serum GSH concentrations and thyroid-related outcomes in treatment-naïve euthyroid women with CAT. Methods: This prospective, non-randomized, open-label, parallel-group comparative interventional study included 50 treatment-naïve euthyroid women with CAT. Participants were allocated to receive either thyroid-directed transdermal PBM (n = 25) or selenium plus vitamin D supplementation (n = 25). The primary outcome was the change in serum GSH concentration. Secondary outcomes included changes in thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), anti-thyroid peroxidase antibodies (anti-TPO), anti-thyroglobulin antibodies (anti-Tg), thyroid volume, and anthropometric parameters. Assessments were performed at baseline (T0), after the intervention period (T1), and three months after intervention completion (T2). Results: A significant time × group interaction was observed for serum GSH concentrations (F = 19.101, p < 0.0001). Significant interactions were also observed for anti-TPO (F = 7.513, p = 0.001), anti-Tg (F = 7.389, p = 0.002), and thyroid volume (F = 13.081, p < 0.0001). In the PBM group, GSH increased from baseline to T1 and remained higher at T2, while TSH, anti-TPO, anti-Tg, and thyroid volume decreased, and FT3 and FT4 increased. No significant longitudinal changes in GSH or thyroid autoantibodies were observed in the supplementation group. No participant in the PBM group required levothyroxine (LT4) initiation during follow-up, whereas 24% of participants in the supplementation group initiated LT4 therapy at T1, with some requiring dose escalation by T2. Conclusions: Thyroid-directed PBM was associated with improved systemic GSH status and favorable changes in thyroid autoimmunity, thyroid function parameters, and thyroid volume compared with selenium plus vitamin D supplementation in treatment-naïve euthyroid women with CAT. These findings suggest that modulation of oxidative stress may represent one potential biological pathway underlying the observed effects of PBM. Larger randomized controlled studies with longer follow-up are required to confirm these findings and define the clinical role of PBM in autoimmune thyroid disease.